A USB 2.0 controller for an ARM7TDM-S processor implemented in FPGA - Difuntorum, John Keithley L.; Matutina, Kristine Marie; Tong, Al Jerome Mervyn (2011)
As technology evolves, advancement in the performance and speed of various computing mechanisms calls for the integration of faster and more reliable data communication interfaces. One of the most widely used interfacing systems today is the Universal Serial Bus interface. USB is a bi-directional, low-cost, low-to-high speed serial interface that is fully compatible with existing peripherals. Our study focused on providing a USB interface for an ARM7TDM-S system. A USB Controller was designed to facilitate communication from a PC to the ARM7TDM-S system and vice-versa. The USB transfer is compliant with the USB 2.0 specifications. All the modules including the USB Controller and ARM7TDM-S were designed in Verilog HDL and implemented into a Virtex 5 FGPA board for testing. Transceiver hardware is included to handle the electrical levels and to provide the connection between the FGPA-based system and the PC host.
Undergraduate student project (B.S. Computer Engineering)--University of the Philippines, Diliman.
Keywords: USB (Computer bus); RISC microprocessors; Field programmable gate arrays; ARM7TDM-S processor; USB 2.0 controller